Extension of Village Head Term of Office in the Village Law Perspective: Governance Implications - Junaedi Imam Subekti; Atik Krustiyati (IHSA Institute, 2026)
The extension of the village head’s term of office under the Village Law has sparked debate over the balance between governance stability and democratic principles at the village level. This article examines the legal regulation of the extension of the village head’s term of office and its implications for village governance from a normative legal perspective. Using legislative, conceptual, and historical approaches, this study analyzes statutory regulations, legal doctrines, and relevant scholarly works through qualitative legal interpretation. The analysis shows that extending the term of office may strengthen administrative stability and policy continuity in village governance. However, it also increases the risk of power concentration when not accompanied by effective oversight mechanisms. The study argues that the extension of the village head’s term of office can be compatible with the principles of good governance only if it is supported by clear implementing regulations that ensure accountability, transparency, and meaningful community participation in village governance